Technology Adoption and User Satisfaction in Industrial Information Systems: Adopsi Teknologi dan Kepuasan Pengguna dalam Sistem Informasi Industri - Prayogi, Dhimas Wahyu; Safirin, Moch. Tutuk (Academia Open, 2025)
General background: The acceleration of digital transformation in Indonesia’s industrial sector requires effective information systems to support governance, data integration, and decision-making. Specific background: The National Industrial Information System (SIINas) was developed to meet these needs; however, its utilization in East Java remains suboptimal due to limited understanding, low awareness, and uneven adoption among industrial companies. Knowledge gap: Existing studies on technology adoption using the Technology-Organization-Environment (TOE) framework rarely examine SIINas, particularly regarding how adoption influences user satisfaction at the regional level. Aims: This study analyzes how technological, organizational, and environmental factors affect SIINas adoption and how adoption subsequently impacts user satisfaction. Results: Using a quantitative approach with PLS-SEM and 76 respondents, findings show that all three TOE dimensions significantly influence technology adoption, with environmental factors having the strongest effect. Adoption also demonstrates a strong, significant impact on user satisfaction. Novelty: This study provides the first integrated TOE–user satisfaction evaluation of SIINas at the provincial level. Implications: The results highlight the need for stronger environmental support, organizational readiness, and technological capability to enhance SIINas adoption and improve user experience within the industrial sector. Highlights: Identifies key technological, organizational, and environmental drivers of SIINas adoption. Demonstrates strong influence of adoption on user satisfaction. Provides the first regional TOE-based evaluation of SIINas in East Java. Keywords: SIINas, Technology Adoption, TOE Framework, User Satisfaction, Industrial Information Systems